Kajian Eksperimen Kuat Tekan Beton Ringan Menggunakan Agregat Bambu dan Bahan Tambah Beton - Endarto, Muhammad Riang; Zulfiar, Muhammad Heri (Jurnal Semesta Teknika, 2010)
The use bamboo as a substitute aggregate is an effort to reduce the density and static load of structural elements. This reseach focuses on the problem related to the specific gravity and compressive strength of the use of bamboo as a lightweight concrete aggregate. Specimens were produced using additive and 10 mm maximum grain size of bamboo agregate as a substitute for split aggregate, in a lightweight concrete composite systems. Variation of bamboo content as a substitute aggregate were selected being 0% (normal), 20%, 40%, 60%, 80% and 100% by weight of split aggregate. The samples are in the form of cylinder (of 15 cm diameter and 30 cm height), while the compression testing were performed after 14 days of treatment. The results showed that the lightweight concrete containing 80% of bamboo aggregate possessing compressive strength 5,86 MPa, which is below the minimum standard of ACI of 17,2 MPa.